Operating RTLS systems in underground workings - Miśkiewicz, Kazimierz; Nowrot, Andrzej; Wojaczek, Antoni (Wydawnictwa AGH, 2019)
The difficult environment conditions of underground mines require the identification of persons present in mining workings. To date, miner location systems applied in several mines only allow a dispatcher to determine the crew working at given level or in given operation area on quantitative basis. The dispatcher has no opportunity to accurately and currently locate the miners who are in the workings. This constitutes a large difficulty in the case of mining disasters and where rescue actions are to be undertaken when miners are trapped underground in workings. Several days spent searching for miners during a recent disaster led to the implementation of a RTLS continuous localization system in especially dangerous areas. This paper discusses the opportunity to use RTLS systems in mines and presents selected first experiments related to operation tests of such RTLS systems that were carried out recently in several mines.
Funkcjonowanie systemu RTLS w wyrobisku podziemnym
Mining - Informatics, Automation and Electrical Engineering
Bibliogr. s. 16.
Keywords: RFID systems; RTLS location systems; radio communication in mining